Study of entrance surface skin dose in veterinary radiology - Veneziani, G. R. (2009)
This study aims the evaluation of the radiation dose levels involved in veterinary radiology and to contribute to review the procedures for performing radiographic exams in animals in the Department of Veterinary Radiology of Faculdade de Medicina Veterinária e Zootecnia of Universidade Estadual Paulista (FMVZ-UNESP/Brazil). The obtained results has shown to be extremely important the assessment of doses involved in veterinary diagnostic radiology procedures both to protect the occupationally exposed workers and to optimize the delivered doses to the animals. © 2009 Springer-Verlag.